2014
DOI: 10.1093/ntr/ntu144
|View full text |Cite
|
Sign up to set email alerts
|

Internet and Telephone Treatment for Smoking Cessation: Mediators and Moderators of Short-Term Abstinence

Abstract: Introduction: This study examined mediators and moderators of short-term treatment effectiveness from the iQUITT Study (Quit Using Internet and Telephone Treatment), a 3-arm randomized trial that compared an interactive smoking cessation Web site with an online social network (enhanced Internet) alone and in conjunction with proactive telephone counseling (enhanced Internet plus phone) to a static Internet comparison condition (basic Internet). Methods: The analytic sample was N = 1,236 participants with compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Increasing smokers’ confidence in their ability to quit was the best mediator. This finding is in line with research on telephone counseling and cellphone interventions that have highlighted the importance of self‐efficacy in achieving abstinence . It extends existing evidence by showing that self‐efficacy plays a key role in text‐messaging interventions, and that utilization of outside resources was not important as a meditational pathway, with the possible exception of the use of medications.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Increasing smokers’ confidence in their ability to quit was the best mediator. This finding is in line with research on telephone counseling and cellphone interventions that have highlighted the importance of self‐efficacy in achieving abstinence . It extends existing evidence by showing that self‐efficacy plays a key role in text‐messaging interventions, and that utilization of outside resources was not important as a meditational pathway, with the possible exception of the use of medications.…”
Section: Discussionsupporting
confidence: 87%
“…The clear result of psychosocial processes playing a key role in conferring the benefit of Text2Quit notwithstanding, much of the variance remains unexplained, similar to other studies of treatment mechanisms underlying smoking cessation . With 65% of the effect still unaccounted for, there are still other ways in which text‐messaging confers benefit.…”
Section: Discussionmentioning
confidence: 72%
“…Abstinence results at 3 months favored the combined web and phone counseling condition although between-group differences did not emerge at 6 months follow-up. Moreover, in a study having relevance to the current research, Graham et al (Cobb & Graham, 2014; Cobb, Niaura, Donaldson, & Graham, 2014; Graham et al, 2013; Graham et al, 2011; Graham et al, 2014) have described results for the iQUITT study, a large smoking cessation RCT, that found a combination of Enhanced Web (interactive plus large social network) and Quitline outperformed both a Basic Web (static text webpages) and the Enhanced Web intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacotherapies appear to enhance long-term abstinence primarily by suppressing withdrawal symptoms, especially craving (e.g., Bolt et al, 2012; Ferguson et al, 2006; Lerman et al, 2002), but other mechanisms may also be implicated (McCarthy et al, 2008; Piper et al, 2008). Research on counseling treatment has fairly consistently supported self-efficacy as a mediator of counseling effects (Graham et al, 2015; Hendricks et al, 2010; McCarthy et al, 2010; Schuck et al, 2014). However, only isolated findings support the roles of other putative mediators: decreased expectations of smoking reward (Schuck et al, 2014), greater avoidance of smoking cues (McCarthy et al, 2010; McCarthy et al, 2008; Schuck et al, 2014), increased perceived partner support (Graham et al, 2015), and reduced guilt and demoralization following repeated lapses (McCarthy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Research on counseling treatment has fairly consistently supported self-efficacy as a mediator of counseling effects (Graham et al, 2015; Hendricks et al, 2010; McCarthy et al, 2010; Schuck et al, 2014). However, only isolated findings support the roles of other putative mediators: decreased expectations of smoking reward (Schuck et al, 2014), greater avoidance of smoking cues (McCarthy et al, 2010; McCarthy et al, 2008; Schuck et al, 2014), increased perceived partner support (Graham et al, 2015), and reduced guilt and demoralization following repeated lapses (McCarthy et al, 2010). This inconsistency may be due to variation in counseling interventions in these studies (e.g., lengths and types of treatment, control conditions, routes of counseling delivery).…”
Section: Introductionmentioning
confidence: 99%